Fenomena Fatherless di Indonesia - Fajriyanti, Aura; Desy Safitri; Sujarwo (Universitas Negeri Surabaya, 2024)
Fatherless can be interpreted as a child who grows and develops without the presence of a father, or a child who has a father but the father does not play a maximum role in the child's development process, in other words, parenting. Indonesia itself is said to rank third in the world as a country with the most fatherless children. This is mostly caused by death leading to orphans, but if his absence is caused by departure from his role as a father, then the child can be said to be orphaned prematurely, a divorce, separation due to problems in the marital relationship, or problems health. This writing uses a qualitative approach with the library research method (literary study) as secondary data. The results of the study show that fatherless has many impacts on children, namely identity crises, children's sexual development, and psychological disorders in children in adulthood.